Does Corporate Governance structure affect firms’ capital structure decisions? An empirical exploration in the context of an emerging market economy - Maniruzzaman, Md.; Zabid Hossain, Syed (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2023)
Abstract: The purpose of the research is to explore whether the corporate governance (CG) structure can influence capital structure (CS) decisions of the listed manufacturing firms in Bangladesh or not. The study covers a period from 2007 to 2020 for Dhaka Stock Exchange (DSE) listed 82 manufacturing companies and uses descriptive statistics and the OLS regression model to catch the effects of CG structure on CS. This study finds that board size and firm age have a significant positive effect on CS. Contrarily, board freedom, audit committee, and gender diversity have a significant negative impact on CS. CEO duality and concentrated ownership have shown a negative but insignificant influence on CS. Though the agency and resource dependence theories propose a positive link between the CG structure and CS, this study shows all CG devices except firm age and size have a negative impact on CS. The theoretical predictions differ significantly from the empirical evidence. This study also examines the CG-CS affinity using the data before 2012 and after the mandatory CG code of 2012, which is still unexamined.